Telecommuting and cyberloafing in the Ghanaian context: The role of employees emotional exhaustion - Kwesi Amponsah-Tawiah; Justice Mensah; Nana Kojo Ayimadu Baafi (Organization Management Journal (OMJ), 2023)
Purpose - This study aims to examine the relationship between telecommuting and cyberloafing among Ghanaian workers. In addition, the study investigated the moderating role of emotional exhaustion on telecommuting and cyberloafing. Design/methodology/approach - The study collected quantitative data from 945 employees in banks, telecommunication and insurance sectors of the Ghanaian economy. Data was entered using SPSS v.23 and analysed with Process Macro v3.5. Findings - The results indicate that there is a significant positive relationship between telecommuting and cyberloafing. It also found out that emotional exhaustion has a significant negative relationship with cyberloafing. Furthermore, emotional exhaustion moderated the relationship between telecommuting and cyberloafing. Organisations are not necessarily required to be in a particular location to achieve their goals. Through practices such as telecommuting, organisations are able to unleash the creative and innovative abilities of employees and also improve their psychological well-being for greater gains. Practical implications - The practice of telecommuting psychologically empowers the individual giving some decision-making latitudes to one and making one responsible and accountable for their actions and inactions. Also, individuals who are giving the chance to telecommute will only engage in cyberloafing behaviours when they are emotionally exhausted. Thus, it is important to create conditions that establishes equilibrium and creates harmony between the individual and the work, hence eliminating any feeling of emotional exhaustion and reaping the full benefits of telecommuting. Originality/value - To the best of the authors' knowledge, this study is the first to examine the role of emotional exhaustion in the relationship between telecommuting workers and their engagement in cyberloafing.
Keywords: 650; Cyberloaf; Emotional exhaustion; Job demand resource; Management by objectives; Telecommute